2020
DOI: 10.1016/j.reprotox.2020.04.028
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Clinician James Lind Alliance Partnership to Identify Research Priorities for Hyperemesis Gravidarum

Abstract: Objective There are many uncertainties surrounding the aetiology, treatment and sequelae of hyperemesis gravidarum (HG). Prioritising research questions could reduce research waste, helping researchers and funders direct attention to those questions which most urgently need addressing. The HG priority setting partnership (PSP) was established to identify and rank the top 25 priority research questions important to both patients and clinicians. Methods Following the James Lind Alliance (JLA) methodology, an HG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Such a wide risk prediction bracket for a condition with substantial biopsychosocial impacts makes informed decision‐making regarding subsequent pregnancies difficult. Patients have expressed a desire for research to provide a definitive recurrence risk and recently this was also recognized as a priority research question by a priority‐setting partnership 6,7 . Furthermore, there is evidence suggesting that early treatment and lifestyle preparation strategies may reduce the overall severity of the condition 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a wide risk prediction bracket for a condition with substantial biopsychosocial impacts makes informed decision‐making regarding subsequent pregnancies difficult. Patients have expressed a desire for research to provide a definitive recurrence risk and recently this was also recognized as a priority research question by a priority‐setting partnership 6,7 . Furthermore, there is evidence suggesting that early treatment and lifestyle preparation strategies may reduce the overall severity of the condition 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…With this study we are addressing two of the top 10 priority HG research questions that were recently identified by patients and clinicians, indicating the urgency of the need for guidance in the consequences of nutritional deficiency among women with HG. (30) This study can help meet patients' need for information on the long term consequences of undernutrition associated with HG for their offspring -a source of significant maternal distress. (31) Despite the small sample size, sensitivity analysis did not show any differences between MOTHER participants with and without cord blood samples available.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Vitamin K was included in parenteral nutrition which was started at 15 weeks gestation. The median gestational age when vitamin K supplementation was commenced was 14 weeks (interquartile range 12-16) compared with the median gestational age of 19 weeks (interquartile range [16][17][18][19][20][21][22][23][24][25][26] when fetal anomalies were detected on perinatal ultrasound (Table 5).…”
Section: Neonatal Complications Due To Hyperemesis Gravidarumrelated Vitamin K Deficiencymentioning
confidence: 99%
“…The fact that HG has a profound impact on nutritional intake, sometimes necessitating enteral or parenteral nutrition, has raised concerns about the possibility that vitamin K deficiency can also occur in pregnancies complicated by HG (1,17,18) . Recently, the identification of the immediate and long-term effects of HG for pregnant women and their offspring were selected as urgent research questions by patients and health care professionals, which triggered the current work (19) . In this systematic review, we aimed to summarise the available literature on HG-related maternal and neonatal vitamin K deficiency and determine the relevance of measuring vitamin K-related coagulopathy factors or prothrombin time (PT) in routine work-up for women with HG.…”
mentioning
confidence: 99%